2004
DOI: 10.1007/s00442-004-1504-8
|View full text |Cite
|
Sign up to set email alerts
|

Are nectar-robbers mutualists or antagonists?

Abstract: As "exploiters" of plant-pollinator mutualisms, nectar-robbers remove rewards (nectar) without providing pollination services. Though one might expect nectar-robbing to be costly to plants, it may instead benefit plants by indirectly increasing pollen dispersal. I investigated the direct effects of nectar-robbing bees ( Xylocopa californica) on floral rewards and behaviors of pollinators visiting desert willow ( Chilopsis linearis) and indirect effects of robbing on the reproductive success of the plant. Necta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 32 publications
1
58
2
2
Order By: Relevance
“…Our observations in the field indicated that after robbing the flowers in one patch, carpenter bees fly greater distances before landing to rob in another patch than the distance flown by the other main pollinator species between 2 pollination bouts. This behavior is similar to that of bumblebees and may probably increase the distance of pollen flow and also the out-crossing rates (Zimmerman and Cook 1985;Gliddon and Saleem 1984;Fenster 1991;Richardson 2004; but see Irwin 2003). In this case nectar robbing may be beneficial to G. longituba by indirectly contributing to increased heterozygosity and genetic diversity in its populations.…”
Section: Effect Of Nectar Robbing On Male-female Fitnessmentioning
confidence: 70%
“…Our observations in the field indicated that after robbing the flowers in one patch, carpenter bees fly greater distances before landing to rob in another patch than the distance flown by the other main pollinator species between 2 pollination bouts. This behavior is similar to that of bumblebees and may probably increase the distance of pollen flow and also the out-crossing rates (Zimmerman and Cook 1985;Gliddon and Saleem 1984;Fenster 1991;Richardson 2004; but see Irwin 2003). In this case nectar robbing may be beneficial to G. longituba by indirectly contributing to increased heterozygosity and genetic diversity in its populations.…”
Section: Effect Of Nectar Robbing On Male-female Fitnessmentioning
confidence: 70%
“…Bertholletia excelsa Ă© uma espĂ©cie de planta com sistema reprodutivo auto-incompatĂ­vel (MauĂ©s 2002), sendo, portanto, efi cientemente polinizada somente se seus polinizadores visitarem outros indivĂ­duos na população (Goulson 1999, Singer & Koehler 2003, Richardison 2004, Tangmitcharoen et al 2006. Desse modo, Ă© intrigante considerar que as abelhas sem ferrĂŁo, embora estejam afetando a atividade de forrageio dos polinizadores em questĂŁo, possam tambĂ©m, atĂ© certo ponto, contribuir para a polinização cruzada da castanheira.…”
Section: Discussionunclassified
“…While it is possible that several of these were nectar robbers (Richardson 2004), honeybees were recorded in this study and have been shown as important pollinators of other Aloe species, (Botes et al 2009a;Symes et al 2009). They made up by far the greatest proportion of recorded insect visitors so, like in A. greatheadii var.…”
Section: Inflorescence Visitors and Behaviourmentioning
confidence: 99%